Effect of Variety and Level of Phosphorus on the Yield and Yield Components of Lentil - Datta, SK; Sarker, MAR; Uddin, FMJ (International Journal of Agricultural Research, Innovation and Technology, 2013)
The experiment was carried out to study the effect of variety and level of phosphorus fertilizer on the yield and yield components of lentil at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during October 2009 to March 2010. Three lentil varieties viz. BINA masur 2, BINA masur 3 and BARI masur 4 and four levels of phosphorus viz. 0 kg P ha-1 (P0), 15 kg P ha-1 (P15), 30 kg P ha-1 (P30) and 45 kg P ha-1 (P45) were used in this experiment. Varieties showed significant influence on the all characters except plant height. The highest seed yield (1165 kg ha-1) was observed in BARI masur 4, and the lowest seed yield (1028 kg ha-1) was found in BINA masur 3. Phosphorus fertilizer had a significant effect on all the plant characters studied except 1000 seed weight. The highest seed yield (1222kg ha-1) was observed in P45 (45 kg P ha-1) treatment and the lowest seed yield (893 kg ha-1) was found in P0 treatment. In case of interaction, effect of cultivar and phosphorus fertilizer doses had a significant effect on all the plant characters studied except seeds pod-1 and 1000-seed weight. The highest seed yield (1317 kg ha-1) was obtained in V3 X P45 treatment, and the lowest seed yield (830 kg ha-1) was observed in V2 X P0 treatment combination. Among the varieties BINA masur 2 and BARI masur 4 were superior to BINA masur 3 in respect of yield performance with 30 kg P ha-1. BARI masur 4 fertilized with 30 kg P ha-1 produced the highest seed yield. Int. J. Agril. Res. Innov. & Tech. 3 (1): 78-82, June, 2013 DOI: http://dx.doi.org/10.3329/ijarit.v3i1.16097